DYNAMICS OF FUNCTIONAL TRAINING OF BIATHLETES DURING THE MACRO CYCLE - Buy, I. V. (Rehabilitation and Recreation, 2023)
The goal is to analyze indicators of functional fitness of female biathletes at the stage of specialized basic training. Methods. Analysis and generalization of special scientific literature (for studying and substantiating the initial provisions of the research, defining its problem field); empirical level of research – pedagogical observation: during the research, more than 80 educational and training classes in biathlon were held; pedagogical experiment; medical and biological methods; methods of mathematical statistics – for processing the research results, proving the statistical significance of the results. Results. The article analyzes the characteristic features of the functional fitness of female biathletes during the annual macrocycle. The need for the formation and enhanced development of the functional readiness of female biathletes at the early stages of sports training is substantiated. Data on the functional fitness of female biathletes who are at the stage of specialized basic training were studied according to the following indicators: maximum oxygen consumption, vital capacity of the lungs, vital index, Harvard step test, physical capacity. The initial level of physical performance, maximum oxygen consumption, vital capacity of the lungs in dynamics during the annual macrocycle were analyzed. A comparison of the indicators obtained at the beginning of the experiment and at the end of the experiment with the criteria for assessing physical capacity according to different authors was made. Conclusions. It was found that the results of the researched group of female biathletes at the stage of specialized basic training correspond to a high level of functional fitness according to all criteria.